The Impact of Ascending Levels of Crude Oil Pollution on Growth of Olive ( Olea europaea Linn) Seedlings - Ali, B. A. A .; Ali, H . H.; Shaker, G . A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A study on the impact of ascending levels of crude oil on the growth of transplanted seedlings ( March2005 ) of Olive (Olea europaea Linn) was carried out at the experimental area of Iraq Natural History Museum and Research centre / Baghdad University (Bab-Al-Madham –Baghdad) grown under field condition and continued till April 2008.The experiment was laid out in complete randomized design ( CRD ) with five levels of pollution (0.0 , 0.5 , 1.0 , 2.0 and 3.0 liter / seedling ) poured at the soil surface , each seedling represented one replicate and was replicated four times . Data collected from the experiment were visual symptoms , percents of seedlings death, plant height and total dry weight of harvested plants. The results indicated that crude oil pollution caused an adverse effect on the Olive (Olea europaea Linn). The crude oil led to leaf chlorosis , dryness and death of seedlings. The adverse effects were proportional with the levels of pollution. Plant heights and total dry weights were significantly reduced (p< 0.05) as a consequence of pollution. Results of the study indicated that the effect of pollution clearly appeared after three weeks at the high levels then the symptoms extended to lower levels during the first six months. The study showed that treated plants with low levels of crude oil pollution were less growth but survived and stayed alive, while the higher levels led to seedlings death. It was obvious that the adversely affected plants could not be able to recover even after 27 months after pollution, the time of the experiment.